5
$\begingroup$

Evaluate the limit of:

$$\sum_{n=1}^{\infty}\frac{n^2}{n!}$$

Hints I am given:

1- The exponential series of type $\sum_{n=0}^{\infty}\frac{x^n}{n!}$ converge into $e^x$ for any $x\in R$

2- Any series of type $\sum_{n=0}^{\infty}\frac{P(n)}{n!}x^n$ , being $P(n)$ a polynomial of any level and $\forall x\in R$, it also converges.

3- $\sum_{n=1}^{\infty}a_{n-1}=\sum_{n=0}^{\infty}a_{n}$

What is the limit of this series?

According to the hints it is convergent, this is what I tried so far:

$\sum_{n=1}^{\infty}\frac{n^2}{n!}=\sum_{n=1}^{\infty}\frac{n^2}{n(n-1)!}=\sum_{n=1}^{\infty}\frac{n}{(n-1)!}$

Applying hint 3:

$\sum_{n=0}^{\infty}\frac{n+1}{n!}$

Split the series in 2:

$\sum_{n=0}^{\infty}\frac{n+1}{n!}=\sum_{n=0}^{\infty}\frac{n}{n!}+\sum_{n=0}^{\infty}\frac{1}{n!}$

Applying hint 1, with $x=1$ to the second part:

$\sum_{n=0}^{\infty}\frac{n+1}{n!}=e+\sum_{n=0}^{\infty}\frac{n}{n!}$

I dont know how to keep going, I know that the series $\sum_{n=0}^{\infty}\frac{n}{n!}$ converges into $e$ therefore the result of the whole series is 2 times $e$ but I dont understand why!

$\endgroup$
  • 6
    $\begingroup$ $$\sum_{n\geq 0}\frac{n}{n!}=\sum_{n\geq 1}\frac{n}{n!}=\sum_{n\geq 1}\frac{1}{(n-1)!}=\sum_{m\geq 0}\frac{1}{m!}=e.$$ $\endgroup$ – Jack D'Aurizio Oct 31 '18 at 21:13
  • 4
    $\begingroup$ Additionally, "the limit of $\sum_{n\geq 1}f(n)$" is redundant since $\sum_{n\geq 1}f(n)$ is already a limit, $\lim_{N\to +\infty}\sum_{n=1}^{N}f(n)$. So "the limit of $\sum_{n=1}^{N}f(n)$ as $N\to +\infty$" or just "$\sum_{n\geq 1}f(n)$". $\endgroup$ – Jack D'Aurizio Oct 31 '18 at 21:15
  • $\begingroup$ Note that $n^2=n(n-1)+n$ - that's how I would begin this. (Polynomials in $n$ can be expressed in a similar way) $\endgroup$ – Mark Bennet Oct 31 '18 at 21:23
  • $\begingroup$ math.stackexchange.com/questions/1711318/… $\endgroup$ – lab bhattacharjee Nov 1 '18 at 0:51
4
$\begingroup$

$S_n = \sum_{k=1}^{n} \frac{k^2}{k!}$

Writing $k! = k(k-1)!$, we get

$S_n = \sum_{k=1}^{n} \frac{k}{(k-1)!} = \sum_{k=1}^{n} \frac{k-1}{(k-1)!} +\sum_{k=1}^{n} \frac{1}{(k-1)!}$.

Using $(k-1)! = (k-1)(k-2)!$, this can be further simplified to:

$S_n = \sum_{k=2}^{n} \frac{1}{(k-2)!} + \sum_{k=1}^{n} \frac{1}{(k-1)!}$.

Each of the above summations converges to $e$ as $n \rightarrow \infty$, so we get $\text{lim}_{n \rightarrow \infty}S_n = 2e$.

$\endgroup$
  • $\begingroup$ You go from $\sum_{n=1}^{\infty} \frac{n-1}{(n-1)!}$ to $\sum_{n=2}^{\infty} \frac{1}{(n-2)!}$ and change the summation's first item to 2, why can you do this? $\endgroup$ – user605734 MBS Oct 31 '18 at 21:44
  • 1
    $\begingroup$ @user605734MBS, because ${n-1\over(n-1)!}=0$ for $n=1$ and $1\over(n-2)!$ for $n\ge2$. $\endgroup$ – Barry Cipra Oct 31 '18 at 21:49
  • 2
    $\begingroup$ It's because the first term of the summation is 0 ($\frac{n-1}{(n-1)!} = 0$ for $n=1$), so changing the starting index to 2 won't make a difference. $\endgroup$ – Aditya Dua Oct 31 '18 at 21:50
  • $\begingroup$ Okay I'll make sure to change the index first from now on, I was stuck there because I simplified first and then tried to change the inex, but I got $\sum_{n=1}^{\infty} \frac{1}{(n-2)!}$ then the first item would be $\frac{1}{(-1)!}$ Which is undefined. $\endgroup$ – user605734 MBS Oct 31 '18 at 21:54
  • 1
    $\begingroup$ $S_n$ is not a function of $n$. $\endgroup$ – marty cohen Nov 1 '18 at 1:16
3
$\begingroup$

$$ f(x) = \sum_{n=0}^\infty \frac{n^2 x^n}{n!} $$ can be expressed as $$ f(x) = x \frac{d}{dx}\left(x\frac{d}{dx}e^x\right) = x \frac{d}{dx}(xe^x) = e^x(x+x^2). $$ Therefore your sum is $f(1)=2e$.

$\endgroup$
3
$\begingroup$

$$\begin{matrix} \\&\dfrac1{0!}&+&\dfrac1{1!}&+&\dfrac1{2!}&+&\dfrac1{3!}&+&\dfrac1{4!}&+&\cdots \\+&&&\dfrac1{0!}&+&\dfrac1{1!}&+&\dfrac1{2!}&+&\dfrac1{3!}&+&\cdots \\\hline =&\dfrac1{0!}&+&\dfrac{1+1}{1!}&+&\dfrac{1+2}{2!}&+&\dfrac{1+3}{3!}&+&\dfrac{1+4}{4!}&+&\cdots \\=&\dfrac1{0!}&+&\dfrac{2}{1!}&+&\dfrac{3}{2!}&+&\dfrac{4}{3!}&+&\dfrac{5}{4!}&+&\cdots \\=&\dfrac{1^2}{1!}&+&\dfrac{2^2}{2!}&+&\dfrac{3^2}{3!}&+&\dfrac{4^2}{4!}&+&\dfrac{5^2}{5!}&+&\cdots \end{matrix}$$

$\endgroup$
1
$\begingroup$

As an alternative

$$\sum_{n=1}^{N}\frac{n^2}{n!}=\sum_{n=1}^{N}\frac{n}{(n-1)!}=\sum_{n=0}^{N-1}\frac{(n+1)}{n!}=\sum_{n=0}^{N-1}\frac{n}{n!}+\sum_{n=0}^{N-1}\frac{1}{n!}=\sum_{n=1}^{N-1}\frac{1}{(n-1)!}+\sum_{n=0}^{N-1}\frac{1}{n!}=$$$$=\sum_{n=0}^{N-2}\frac{1}{n!}+\sum_{n=0}^{N-1}\frac{1}{n!} \to e+e=2e$$

$\endgroup$
1
$\begingroup$

$$e^{x}=\sum_{n=0}^{\infty }\frac{x^n}{n!}$$ differentiate it $$e^{x}=\sum_{n=1}^{\infty }\frac{nx^{n-1}}{n!}$$ multiply by $x$ $$xe^{x}=\sum_{n=1}^{\infty }\frac{nx^{n}}{n!}$$ differentiate it again $$xe^{x}+e^x=\sum_{n=1}^{\infty }\frac{n^2x^{n-1}}{n!}$$ let $x=1$ $$1e^{1}+e^1=\sum_{n=1}^{\infty }\frac{n^2}{n!}$$ so $$\sum_{n=1}^{\infty }\frac{n^2}{n!}=2e$$

$\endgroup$
1
$\begingroup$

If $S_k =\sum_{n=1}^{\infty} \dfrac{n^k}{n!} $, then $S_0 =e-1$ and, for $k \ge 0$,

$\begin{array}\\ S_{k+1} &=\sum_{n=1}^{\infty} \dfrac{n^{k}}{(n-1)!}\\ &=\sum_{n=0}^{\infty} \dfrac{(n+1)^{k}}{n!}\\ &=\sum_{n=0}^{\infty} \dfrac1{n!}(n+1)^{k}\\ &=\sum_{n=0}^{\infty} \dfrac1{n!}\sum_{j=0}^k \binom{k}{j}n^j\\ &=\sum_{j=0}^k \binom{k}{j}\sum_{n=0}^{\infty} \dfrac{n^j}{n!}\\ &=\sum_{n=0}^{\infty} \dfrac{1}{n!}+\sum_{j=1}^k \binom{k}{j}\sum_{n=0}^{\infty} \dfrac{n^j}{n!}\\ &=e+\sum_{j=1}^k \binom{k}{j}\sum_{n=1}^{\infty} \dfrac{n^j}{n!}\\ &=e+\sum_{j=1}^k \binom{k}{j}S_j\\ \end{array} $

Setting $k=0$, $S_1 = e$.

Setting $k=1$, $S_2 = e+S_1 =2e$.

Setting $k=2$, $S_3 = e+2S_1+S_2 =5e$.

If $S_k =et_k$ then $t_1 = 1$ and $t_k =1+\sum_{j=1}^k \binom{k}{j}t_j $.

The first few $t_k$ are $1, 2, 5$ and these turn out to be the well-studied Bell numbers - see https://en.wikipedia.org/wiki/Bell_number for a reasonable discussion.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.